Hierarchical 0D−2D Co/Mo Selenides as Superior Bifunctional Electrocatalysts for Overall Water Splitting - Xia, Lu; Song, Hao; Li, Xingxing; Zhang, Xuming; Gao, Biao; Zheng, Yang; Huo, Kaifu; Chu, Paul K. (Frontiers in Chemistry, 2020)
Development of efficient electrocatalysts combining the features of low cost and high performance for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) still remains a critical challenge. Here, we proposed a facile strategy to in-situ construct a novel hierarchical heterostructure composed of 0D-2D CoSe2/MoSe2 by selenization the CoMoO4 nanosheets grafted on a carbon cloth (CC). In such integrated structure, CoSe2 nanoparticles well dispersed and tightly bonded with MoSe2 nanosheets, which can not only enhance kinetics due to the synergetic effects, thus promoting the electrocatalytic activity, but also effectively improve the structural stability. Benefiting from its unique architecture, the designed CoSe2/MoSe2 catalyst exhibits superior OER and HER performance. Specifically, a small overpotential of mV is acquired at a current density of 10 mA·cm -2 for OER with a small Tafel slope of 86.8 mV·dec -1 and the overpotential is 90 mV at a current density of 10 mA·cm -2 for HER with a Tafel slope of 84.8 mV·dec -1 in 1M KOH. Furthermore, the symmetrical electrolyzer assembled with the CoSe2/MoSe2 catalysts depict a small cell voltage of 1.63 V at 10 mA·cm -2 toward overall water splitting.